Digital transformation, gender, and entrepreneurial resilience: A study of women-led SMEs - Siregar, Muhammad Bangun; Dalimunthe, Ritha F; Lumbanraja, Prihatin; Sulistya Rini, Endang (Research Journal in Advanced Humanities, 2026)
Women-led SMEs play a crucial role in promoting inclusive economic growth; however, they often operate within broader social and gendered structures that shape access to resources, opportunities, and digital participation. These conditions frequently limit their competitive advantage, particularly in terms of digital adoption and access to resources. This study aims to examine the mediating role of digitalization in the relationship between entrepreneurial resilience and competitive advantage in women-led SMEs. Using a quantitative, explanatory research design, data were collected from 150 women-led SMEs in North Sumatra, Indonesia. The analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that entrepreneurial resilience has a significant positive effect on digitalization and competitive advantage. Digitalization also has a strong and significant effect on competitive advantage. Furthermore, digitalization has been shown to mediate the relationship between entrepreneurial resilience and competitive advantage. These findings suggest that resilience alone is not sufficient to generate a competitive advantage unless it is transformed through digital capabilities. This study contributes to the literature by integrating perspectives on entrepreneurial resilience and digital transformation within a competitive advantage framework, particularly in the context of women-led SMEs. Practically, the findings highlight the importance of strengthening digital adoption to enhance the competitiveness of women entrepreneurs. Beyond firm-level outcomes, this study also underscores the role of digitalization in supporting broader processes of inclusion and socio-economic empowerment among women entrepreneurs.